An Overview of Autophagy in Hematopoietic Stem Cell Transplantation - Montazersaheb, Soheila; Ehsani, Ali; Fathi, Ezzatollah; Farahzadi, Raheleh; Vietor, Ilja (Frontiers in Bioengineering and Biotechnology, 2022)
Autophagy is a fundamental homeostatic process crucial for cellular adaptation in response to metabolic stress. Autophagy exerts its effect through degrading intracellular components and recycling them to produce macromolecular precursors and energy. This physiological process contributes to cellular development, maintenance of cellular/tissue homeostasis, immune system regulation, and human disease. Allogeneic hematopoietic stem cell transplantation (HSCT) is the only preferred therapy for most bone marrow-derived cancers. Unfortunately, HSCT can result in several serious and sometimes untreatable conditions due to graft-versus-host disease (GVHD), graft failure, and infection. These are the major cause of morbidity and mortality in patients receiving the transplant. During the last decade, autophagy has gained a considerable understanding of its role in various diseases and cellular processes. In light of recent research, it has been confirmed that autophagy plays a crucial role in the survival and function of hematopoietic stem cells (HSCs), T-cell differentiation, antigen presentation, and responsiveness to cytokine stimulation. Despite the importance of these events to HSCT, the role of autophagy in HSCT as a whole remains relatively ambiguous. As a result of the growing use of autophagy-modulating agents in the clinic, it is imperative to understand how autophagy functions in allogeneic HSCT. The purpose of this literature review is to elucidate the established and implicated roles of autophagy in HSCT, identifying this pathway as a potential therapeutic target for improving transplant outcomes.